2019
DOI: 10.5194/bg-2019-90
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrogen use efficiency and N<sub>2</sub>O and NH<sub>3</sub> losses attributed to three fertiliser types applied to an intensively managed silage crop

Abstract: <p><strong>Abstract.</strong> Three different nitrogen fertilizer types, ammonium nitrate, urea and urea coated with a urease inhibitor (Agrotain<sup>®</sup>), were applied at standard rates (70 kg N ha<sup>−1</sup>) to experimental plots in a typical and intensively managed grassland area at Easter Bush Farm Estate (Scotland). The nitrogen use e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, inclusion of urease inhibitors significantly reduced NH 3 losses from 43% to below 14% from urea + NBPT and urea + NBPT + NPPT. This amounts to a 68% reduction in NH 3 compared to an average reduction of 78.5% reported by , 77% by Chambers and Dampney (2009) and approximately 90% by Cowan et al (2019), albeit at lower NH 3 loss levels. The reduction in NH 3 also represents savings in indirect N 2 O associated with emissions of volatilised and re-deposited N. Performance of urea with one or a combination of two urease inhibitors was not significantly different, which is unlike findings of Pasda et al (2016), where the combination of NBPT + NPPT outperformed NBPT in experiments carried out in cropland soils.…”
Section: The Effect Of N Formulation On Ammonia Emissionsmentioning
confidence: 67%
“…However, inclusion of urease inhibitors significantly reduced NH 3 losses from 43% to below 14% from urea + NBPT and urea + NBPT + NPPT. This amounts to a 68% reduction in NH 3 compared to an average reduction of 78.5% reported by , 77% by Chambers and Dampney (2009) and approximately 90% by Cowan et al (2019), albeit at lower NH 3 loss levels. The reduction in NH 3 also represents savings in indirect N 2 O associated with emissions of volatilised and re-deposited N. Performance of urea with one or a combination of two urease inhibitors was not significantly different, which is unlike findings of Pasda et al (2016), where the combination of NBPT + NPPT outperformed NBPT in experiments carried out in cropland soils.…”
Section: The Effect Of N Formulation On Ammonia Emissionsmentioning
confidence: 67%
“…The decrease in the NH 4 + :NO 3 − ratios with increasing N addition rates in the subsurface soil indicated enhanced nitrification rates and a significant positive relationship between leaf δ 15 N of plants and nitrification rates, which was consistent with previous studies on forest ecosystems (Bai et al, 2009; Gurmesa, Wang, et al, 2022; Pardo et al, 2006). Other studies also demonstrated that N addition significantly enhanced N 2 O emissions and NH 3 volatilization, thereby significantly enriching the available soil N pools with 15 N under exogenous N input (Cowan et al, 2019; Kahmen et al, 2008; Xu et al, 2010). However, some studies have reported a decrease in foliar δ 15 N with N addition (Sheng et al, 2019; Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…However, atmospherically deposited N includes various forms of N compounds (Cornell, 2011; Jia et al, 2016; Violaki et al, 2010), including the reduced and oxidized forms of inorganic N, such as ammonium bicarbonate (NH 4 HCO 3 ), NH 4 NO 3 , and ammonium sulfate ((NH 4 ) 2 SO 4 ) (Stevens & Gowing, 2014; Stevens et al, 2011), along with organic N compounds, such as urea (CO(NH 2 ) 2 ), free amino acids, and other methylated amines (Neff et al, 2002). Different N compounds can result in different soil N transformation processes, and consequently, different soil N dynamics and statuses (Cheng et al, 2019; Cowan et al, 2019; Du et al, 2021). They can also induce different extents of soil acidification (Hao et al, 2020; Liu et al, 2021; Schroder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%